Gambaran kebiasaan belajar siswa serta Implikasi nya terhadap Pelayanan Bimbingan dan Konseling - Solihatun Solihatun (Program Studi Bimbingan dan Konseling FKIP UMSU, 2019)
This study aimed to find out the description of students' learning habits in Depok Master High School Indonesia. This research uses descriptive method with a quantitative approach. The population of this study includes all students of class X, XI and XII of Depok Master High School who are enrolled in the 2017-2018 school year as many as 105 students who become research subjects using saturated sampling technique is a sampling technique if all populations are used as samples. Furthermore, to find out the study habits researchers used quantitative methods with a descriptive approach. The instrument uses a Likert scale. The results showed that the study habits of students in SMA Master Indonesia Depok were in the good category that is equal to 54.29% (57 people), good enough category 36.19% (38 people), excellent category 5.71% (6 people ), 3.81% unfavorable category (4 people). The implications of the research results can be used as an analysis of students' needs for the provision of BK services in maintaining student learning habits.